INFECTION OF MYCOBACTERIUM SMEGMATIS WITH D29 PHAGE DNA - Tokunaga, Tohru (The Rockefeller University Press, 1964)
DNA extracted from D29 mycobacteriophage produced plaques when plated on Mycobacterium smegmatis 607. The host bacterium did not require alternation such as conversion to protoplasts; cells susceptible to infection with intact phage were susceptible to DNA. The bases found in calf thymus DNA constituted the bases of D29 DNA, adenine being paired with thymine and guanine with cytosine. The dissymmetry ratio (A + T/G + C) was 0.56, and the buoyant density in CsCl was 1.722 with a GC content of 63.77 per cent. The efficiency of plating of the DNA is very much lower than that of intact D29, and it penetrates the host at a slower rate. As does intact phage, D29 DNA requires calcium ions for productive infection of 607. D29 DNA is significantly inactivated by incubation with RNAase, but the inactivation probably results from a complexing with the DNA rather than from enzyme hydrolysis.